2007
DOI: 10.1291/hypres.30.627
|View full text |Cite
|
Sign up to set email alerts
|

Lower Birth Weight Associated with Current Overweight Status Is Related with the Metabolic Syndrome in Obese Japanese Children

Abstract: The purpose of this study was to clarify the relationship between lower birth weight and current overweight status and to examine the involvement of these factors in the development of the metabolic syndrome (MS) in obese Japanese children. We examined 97 obese boys (mean age 11.3 years; mean percentage overweight [POW] 52.4%) and 29 obese girls (mean age 11.1 years; mean POW 58.3%). The anthropometric measurements, blood pressure, fasting serum insulin and blood glucose, liver enzymes, lipids and lipoproteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…A recent epidemiological study found that LBW children undergo accelerated catch-up growth and tend to be more obese or experience obesity in childhood, which is a strong risk factor for hypertension in adults. 16,[35][36][37] Huxley's study shows that not only being small at birth but also subsequent accelerated postnatal growth tends to lead to high blood pressure in the adolescent period. 6 In a previous study, we also found that accelerated postnatal growth is related to an increased risk of increased blood pressure in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent epidemiological study found that LBW children undergo accelerated catch-up growth and tend to be more obese or experience obesity in childhood, which is a strong risk factor for hypertension in adults. 16,[35][36][37] Huxley's study shows that not only being small at birth but also subsequent accelerated postnatal growth tends to lead to high blood pressure in the adolescent period. 6 In a previous study, we also found that accelerated postnatal growth is related to an increased risk of increased blood pressure in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…As the components of metabolic syndrome, we used the provisional diagnostic criteria of pediatric metabolic syndrome in Japan proposed by the study group of the Ministry of Health, Labor and Welfare of Japan (MetS-JC) [10,11]. The homeostasis model assessment-insulin resistance (HOMA-IR) was used as an indicator of the strength of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…6. In seven studies, 23,26,27,28,35,43,49 TC level was related to BW with two of them 26,28 finding statistically significant differences, and in one study 23 TC was equal in both the SGA and AGA groups. 7.…”
Section: Findings Related To the Barker Hypothesismentioning
confidence: 97%
“…32,35,49,57 4. In eight studies, 24,26,27,28,31,35,49,57 serum insulin levels in older subjects were related to BW; six of them 24,26,27,28,31,35 reported higher mean serum insulin in the SGA than in the AGA group, and two studies. 49,57 reported an inverse relationship between insulin and BW.…”
Section: Findings Related To the Barker Hypothesismentioning
confidence: 99%
See 1 more Smart Citation